2008
DOI: 10.1001/archsurg.143.8.788
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Randomized Studies Evaluating Chewing Gum to Enhance Postoperative Recovery Following Colectomy

Abstract: To compare outcomes following abdominal surgery with or without the use of chewing gum in the early postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
2
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 35 publications
5
56
2
7
Order By: Relevance
“…Although there are relatively low patient numbers and a significant heterogeneity of studies, chewing gum offers significant benefits by reducing the time to pass flatus and the time until first bowel movement. [79][80][81][82] The use of bowel segments in the reconstruction of the urinary tract after cystectomy lead Kouba and colleagues to examine the use of chewing gum following cystectomy. 83 The time to flatus was shorter in patients who received gum compared with controls (2.4 vs. 2.9 days).…”
Section: Prevention Of Prolonged Postoperative Ileusmentioning
confidence: 99%
“…Although there are relatively low patient numbers and a significant heterogeneity of studies, chewing gum offers significant benefits by reducing the time to pass flatus and the time until first bowel movement. [79][80][81][82] The use of bowel segments in the reconstruction of the urinary tract after cystectomy lead Kouba and colleagues to examine the use of chewing gum following cystectomy. 83 The time to flatus was shorter in patients who received gum compared with controls (2.4 vs. 2.9 days).…”
Section: Prevention Of Prolonged Postoperative Ileusmentioning
confidence: 99%
“…Purkayastha and coworkers 31 reported results of a meta-analysis of pooled data extracted from 158 persons participating in 5 RCT that evaluated the effect of chewing gum on the duration of POI, including 2 studies that enrolled subjects undergoing formation of an intestinal stoma. All of the trials incorporated into this systematic review [25][26][27][28]30 were also included in the analysis reported by Noble's group.…”
Section: Question: Does Chewing Gum Shorten the Duration Of Poi In Pamentioning
confidence: 99%
“…The use of chewing gum has emerged as a further, new, novel and simple strategy for preventing postoperative ileus. Several studies have reported on the beneficial effect of using chewing gum after surgery to limit the incidence of ileus [6][7][8] . This study aimed to determine whether gum chewing in the immediate postoperative period facilitates a return to bowel function after cesarean section.…”
Section: Influence Of Gum Chewing On Postoperative Bowel Activitymentioning
confidence: 99%